In Vivo Mouse Models for Hepatitis B Virus Infection and Their Application - Du, Yanqin; Broering, Ruth; Li, Xiaoran; Zhang, Xiaoyong; Liu, Jia; Yang, Dongliang; Lu, Mengji (Frontiers in Immunology, 2021)
Despite the availability of effective vaccination, hepatitis B virus (HBV) infection continues to be a major challenge worldwide. Research efforts are ongoing to find an effective cure for the estimated 250 million people chronically infected by HBV in recent years. The exceptionally limited host spectrum of HBV has limited the research progress. Thus, different HBV mouse models have been developed and used for studies on infection, immune responses, pathogenesis, and antiviral therapies. However, these mouse models have great limitations as no spread of HBV infection occurs in the mouse liver and no or only very mild hepatitis is present. Thus, the suitability of these mouse models for a given issue and the interpretation of the results need to be critically assessed. This review summarizes the currently available mouse models for HBV research, including hydrodynamic injection, viral vector-mediated transfection, recombinant covalently closed circular DNA (rc-cccDNA), transgenic, and liver humanized mouse models. We systematically discuss the characteristics of each, with the main focus on hydrodynamic injection mouse model. The usefulness and limitations of each mouse model are discussed based on the published studies. This review summarizes the facts for considerations of the use and suitability of mouse model in future HBV studies.